2006
DOI: 10.1113/jphysiol.2006.106815
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ channels mediate IKs, a slow K+ current regulating excitability in the rat node of Ranvier

Abstract: Mutations that reduce the function of KCNQ2 channels cause neuronal hyperexcitability, manifested as epileptic seizures and myokymia. These channels are present in nodes of Ranvier in rat brain and nerve and have been proposed to mediate the slow nodal potassium current I(Ks). We have used immunocytochemistry, electrophysiology and pharmacology to test this hypothesis and to determine the contribution of KCNQ channels to nerve excitability in the rat. When myelinated nerve fibres of the sciatic nerve were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
222
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(240 citation statements)
references
References 53 publications
14
222
2
2
Order By: Relevance
“…In the amphibian (frog) myelinated axon (Frankenhaeuser and Huxley, 1964), there is large fast potassium current at the node of Ranvier. But in the mammalian myelinated axon the nodal potassium current is very small and mainly consists of a slow potassium current (Roper and Schwarz, 1989;Schwarz et al, 2006). The SE model (Rattay and Aberham, 1993;Schwarz and Eikhof, 1987) used in this study only incorporated a small fast potassium current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the amphibian (frog) myelinated axon (Frankenhaeuser and Huxley, 1964), there is large fast potassium current at the node of Ranvier. But in the mammalian myelinated axon the nodal potassium current is very small and mainly consists of a slow potassium current (Roper and Schwarz, 1989;Schwarz et al, 2006). The SE model (Rattay and Aberham, 1993;Schwarz and Eikhof, 1987) used in this study only incorporated a small fast potassium current.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study using the CRRSS model (Zhang et al, 2006b), which was derived from mammalian (rabbit) myelinated axon and did not incorporate any potassium current (Chiu et al, 1979), completely failed to simulate the nerve conduction block, further indicating a role of the potassium current. Although the small fast potassium current at the node of Ranvier of the mammalian myelinated nerve may be of importance in nerve conduction block, investigating the role of the slow potassium current is definitively warranted due to its dominant presence at the node of Ranvier (Roper and Schwarz, 1989;Schwarz et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…KCNQ2 is also responsible for a slow K ϩ current that regulates excitability in neurons and axons. 122 Studies with expressed mutated channel subunits show that BFNC mutations result in a loss of K ϩ currents, making BFNC a haploinsufficiency syndrome. Although the neonatal seizures in BFNC resolve by 3 months of age, BFNC is associated with an enhanced incidence (up to 16%) of various forms of epilepsy later in life, so that KCNQ2 and KCNQ3 can be considered epilepsy susceptibility genes.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…In our experiments, late subexcitability decreased only at higher concentrations of propofol. Since previous studies showed that late subexcitability can be specifically suppressed by blocking slow potassium currents (Schwarz et al, 2006) we may assume that propofol also affects these slow potassium currents.…”
Section: Accepted M Manuscript 10mentioning
confidence: 99%
“…Underlying mechanisms are complex and involve mainly sodium conductances at short interstimulus intervals (Hodgkin and Huxley, 1952), and capacitive charging of the internode (Barrett and Barrett, 1982), periaxonal accumulation of potassium (Kocsis et al, 1983) and slow potassium conductances at longer interstimulus intervals (e.g. late subexcitability) (Stys and Waxman, 1994;Schwarz et al, 2006).…”
Section: Accepted M Manuscript 10mentioning
confidence: 99%